Joint Recommendations for the Public Health Informatics Infrastructure. Issue 5 (September 2015) - Miller, Corinne; Ishikawa, Charles; DeLeon, Matthew; Huang, Monica; Ising, Amy; Bakota, Eric
<x xml:space="preserve">Abstract</x> This article presents a consensus statement from the Joint Public Heath Informatics Taskforce for the public health informatics infrastructure.